Student Engagement and Empowerment (SEE) Project, Washington, 2014-2019 - Lyon, Aaron R. ([Verlag nicht ermittelbar], 2021)
Discipline in schools is typically disproportionate, reactive and punitive. Evidence-based strategies that have been recently developed focus on shifting schools to a more proactive and positive approach by detecting warning signs and intervening early. This project evaluates the implementation of an evidence-based intervention to improve students' mindsets and feelings of school belonging. This grant-funded project was designed to enhance school capacity to implement a Tier 2 intervention, Student Engagement and Empowerment (SEE), to improve student attendance, behavior, and achievement, while simultaneously evaluating the effects of this intervention. The intervention and research project were individualized to fit existing school operations in the school district. A grant-funded coach supported delivery of SEE at each school for the duration of the 3-year grant. SEE was delivered by trained teachers in the classroom over the course of a seven-session curriculum. The overarching project goal was to scale up and simultaneously evaluate a Tier 2 intervention that could be sustained after completion of the grant. The originally proposed research procedures consisted of an evaluation of the effects of the SEE program on the outcomes of students at elevated risk for disciplinary action and school dropout. Outcome data was collected for at-risk students in classrooms delivering the SEE program, and a comparison sample of at-risk students in classrooms not delivering the SEE program. Researchers initially hypothesized that students receiving the program would evidence a greater sense of belonging to school, endorse greater growth mindset, have better attendance and fewer suspensions/expulsions and course failure, and have better behavioral outcomes than students in the comparison group.